Evaluation of molecular changes of distal organs after small bowel transplantation - Urban, Peter; Rabajdová, Miroslava; Feterik, Štefan; Bódy, Gabriel; Granda, Tatiana; Mareková, Mária; Veselá, Jarmila (Physiological research, 2018)
The ischemia and reperfusion of a jejunal graft during transplantation triggers the stress of endoplasmic reticulum thus inducing the synthesis of pro-inflammatory cytokines. Spreading of these signals stimulate immunological reactions in distal tissues, i.e. lung, liver and spleen. The aim of this study was to detect the molecular changes in liver and spleen induced by transplanted jejunal graft with one or six hours of reperfusion (group Tx1 and Tx6). Analysis of gene expression changes of inflammatory mediators (TNF-alpha, IL-10) and specific chaperones (Gadd153, Grp78) derived from endoplasmic reticulum (ER) was done and compared to control group. The qRT-PCR method was used for amplification of the specific genes. The levels of corresponding proteins were detected by Western blot with immunodetection. Protein TNF-alpha was in liver tissue significantly overexpressed in the experimental group Tx1 by 48 % (p<0.001). In the group Tx6 we found decreased levels of the same protein to the level of controls. However, the protein concentrations of TNF-alpha in spleen showed increased levels in group Tx1 by 31 % (p<0.001) but even higher levels in the group Tx6 by 115 % (p<0.001) in comparing to controls. Our data demonstrated that the spleen is more sensitive to post-transplantation inflammation than liver, with consequent stress of ER potentially inducing apoptosis and failure of basic functions of lymphoid tissue.
Keywords: slezina; Jejunum; Inflammation Mediators; jejunum; náhodné rozdělení; zvířata; Rats; mužské pohlaví; mikrochirurgie; Spleen; Random Allocation; Rats, Wistar; krysa rodu Rattus; potkani Wistar; Liver; Microsurgery; mediátory zánětu; Animals; játra; Male